Bimbingan Dan Konseling Bagi Anak Dengan Gangguan Autistic Spectrum Disorder - Adinda Putri Maharani Nst; Maya Widya Rizky Pasaribu; Emmi Ayu Lestari; Pira Hesti; Nurul Ramadhan; Rafael Lisinus Ginting (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Children on the autism spectrum have quite serious growth and development problems. However, they have the same rights in the field of education, so we often encounter them in schools, both special schools and general (inclusive) schools. Autistic children need support from various parties to optimize their abilities. The development of autistic children is not like children in general, often forming certain patterns and requiring a lot of consistency. Therefore, assisted schools require collaboration with various parties, especially families, where communication with children is very close. Collaboration between schools and families through guidance and counseling also facilitates and helps families, especially parents, to build relationships and take appropriate actions in everyday life. This research uses a library observation method from a number of current relevant sources. This research develops a model for implementing general guidance and counseling involving families, especially parents, to optimize children's abilities.